The Influence Of Health Promotion About Health Protocols Of Covid-19 Transmission Prevention Toward Society Perception To Prevent Covid-19 Transmission - Santoso, Meti Haksarani; Muhammad Ali Sodik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2020)
The spread of COVID-19, which has reached all provinces in Indonesia with the number of cases and the number of deaths increasing, certainly has an impact on the political, economic, social, cultural, defense and security aspects, as well as the welfare of the people in Indonesia. The COVID-19 situation is still at very high risk at the global and national level. Therefore, guidelines are needed in efforts to prevent and control COVID-19 to provide guidance for health workers to stay healthy, safe, and productive, and that all Indonesians receive services that meet standards. Public awareness to use masks, wash hands, maintains distance may decrease due to limited knowledge and limited information media provided. For this reason, the government was very massive in providing information through advertisements, billboards and others about health protocols in preventing COVID-19. The research purpose was to determine the influence of health promotion about health protocols of Covid-19 transmission prevention toward society perception to prevent COVID-19 transmission in Plumpungrejo Hamlet, Plumpungrejo Village, Kademangan District of Blitar Regency. The research design used observational with a cross sectional approach. The populations were all residents of Plumpungrejo Hamlet with comorbid amount 43 people. The sampe size was 32 respondents with purprosive sampling technique. The statistical test used for data analysis in this study was a simple logistic regression test with a degree of confidence = 0.05. The results showed there was an influence of health promotion about health protocols of Covid-19 transmission prevention in many shapes toward society perception to prevent COVID-19 transmission in Plumpungrejo Hamlet of Plumpungrejo Village of Kademangan District Blitar Regency. The conclusion this research is with the influence of health promotion on people's perceptions, it is hoped that the regional government will continue to providing the information through appropriate strategies so as to reduce the spread of COVID-19 transmission.